Encyclopedia of archaeology : History and discoveries - Murray, Tim 1955- (New Delhi : Bhavana Books & Prints, 2004)
"This three-volume work bridges a long-existing gap by successfully filling the space between scholarly and popular coverage. Taking a global perspective, this 500-entry set contains articles on the full range of archaeological knowledge, including great discoveries, significant archaeologists, important organizations, major geographical areas, and key concepts."--"Outstanding Reference Sources," American Libraries, May 2002.
v. 1. A - D -- v. 2. E - M -- v. 3. N - Z.
Includes bibliographical references and index.
Keywords: Archaeology -- History -- Encyclopedias; Archaeologists -- Biography -- Encyclopedias; Antiquities -- Encyclopedias; Historic sites -- Encyclopedias; Excavations (Archaeology) -- Encyclopedias